Optimizing sports activities on students’ mental health and motivation: a person-based framework-based mixed-methods approach - Fajar Raya Ferdinal Kusuma Bakti; Siti Nurrochmah; Lulut Gilang Saputra; Lalu Moh Yudha Isnaini (Multilateral : Jurnal Pendidikan Jasmani dan Olahraga, 2026)
Background. Mental health problems and declining academic motivation are increasingly prevalent among college students, while evidence regarding the role of physical activity in supporting psychological well-being remains limited. Objectives. This study examined the influence of physical activity on college students’ mental health and academic motivation. Method. A sequential explanatory mixed-methods design was employed. Quantitative data were collected from 199 college students using the DASS-21, Academic Motivation Scale (AMS), and Positive and Negative Affect Schedule (PANAS), followed by semi-structured interviews. Quantitative data were analyzed using descriptive statistics, correlation, regression, and t-tests, while qualitative data were analyzed thematically. Results. Students reported low depression, moderate anxiety and stress, and high exercise motivation. Exercise motivation was significantly associated with lower psychological distress, whereas exercise frequency and duration did not significantly predict stress levels. Qualitative findings highlighted the importance of personal relevance, autonomy, and social support in maintaining physical activity and promoting psychological well-being. Conclusion. Exercise motivation plays a more important protective role than activity volume alone in supporting college students’ mental health and academic motivation. These findings provide evidence for developing person-centered physical activity programs in higher education.